Why People Don’t Use Facebook Anymore? An Investigation Into the Relationship Between the Big Five Personality Traits and the Motivation to Leave Facebook - Hong, Seoyeon; Oh, Sookwang Klive (Frontiers in Psychology, 2020)
This study linked the big five personality traits with motivational factors to leave Facebook based on a survey of 218 former Facebook users. The big five were related with eight main factors retrieved from existing literature. Results showed that neuroticism was positively related to addiction, banality, peer pressure, and privacy while conscientiousness was negatively related to peer pressure, addiction, annoyance, and emergence of new platforms. Openness was positively related with banality but negatively with addiction and peer pressure. Theoretical and practical interpretations are also discussed.